Crisis of character a White House Secret Service officer discloses his firsthand experience with Hillary, Bill, and how they operate - Byrne, Gary J; Schmidt, Grant M (New York Center Street, 2016)
While serving as a Secret Service Officer, Gary Byrne protected President Bill Clinton and the First Family in the White House and outside the Oval Office. There, he saw the political and personal machinations of Bill and Hillary Clinton and those who were fiercely loyal to them. Now Byrne provides a firsthand account of the scandals -- known and unknown -- and daily trials ranging from the minor to national in scale
The vase -- The Air Force security police -- Club Fed -- To the White House -- Meet the new boss -- The boy from Hope, Arkansas -- "Billary" -- Clinton world -- Oklahoma City -- Mole -- Wild Bill -- USSS work environment -- Tours and JJRTC -- Mud drag: Part I -- Mud drag: Part II -- "Commence firing!" -- New skies -- Cyprus
1
Keywords: Byrne, Gary J; Clinton, Bill -- 1946-; Clinton, Hillary Rodham; United States -- Secret Service -- Officials and employees -- Biography; Character; Political corruption -- United States -- History -- 20th century; Political corruption -- United States; Political ethics -- United States; Presidents -- Protection -- United States; Presidents' spouses -- United States; Secret service -- United States; United States -- Politics and government -- 1993-2001; Biographies